The impact of bacillus sp. NTLG2-20 and reduced nitrogen fertilization on soil properties and peanut yield - Chuong, Nguyen Van (Communications in Science and Technology, 2024)
The excessive use of nitrogen (N) fertilizers has led to farmland degradation and reduced crop yields. To address this drawback, reducing the amount of nitrogen fertilizer and Bacillus sp. NTLG2-20 inoculant are the optimal cultivation method. The impact of different N rates (0, 20, and 40 kg ha-1) combined with the Bacillus sp. NTLG2-20 inoculant on soil chemical properties, growth, development, and peanut yield was designed in the field in Phuoc Hung commune, An Phu district from May to August 2023. The field experiment was designed with 6 treatments and 4 replications. The research results showed that different N rates adequately augmented soil chemical traits such as pH, cation exchange capacity (CEC), soil organic matter (SOM), total N, available phosphorous (AP), and exchangeable potassium (EK). Furthermore, different N fertilizers rates combined with Bacillus sp. NTLG2-20 inoculant adequately augmented plant height, number of leaves, total chlorophyll, nodulous number and weight per groundnut plant. Reducing N fertilizer application by 50% (20 kg N ha-1) was the optimal N reduction rate when combined with the Bacillus sp. NTLG2-20, which resulted in 17.6% higher peanut yield compared to no N application and no difference compared to 100% of recommended N application (P<0.01)). Bacillus sp. NTLG2-20 inoculant increased peanut yield by 19.6% when compared to no Bacillus sp. NTLG2-20 inoculant (P<0.01). Nitrogen – fixing ability of Bacillus sp. NTLG2-20 promoted peanut yield and reduced fifty percentage of the N fertilizer application. Bacillus sp. NTLG2-20 is the promising species for the production of biological fertilizer in the future.